PENGEMBANGAN PERANGKAT PEMBELAJARAN MATERI HIMPUNAN MODEL RESIK BERBASIS SCIENTIFIC DI SMP - Putriyani Samsul; Hafsyah Hafsyah; Suparman Suparman (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
This research aims to produce learning tools on the RESIK learning model and scientific approach that is valid, practical, and effective. The learning tool used for home studying during the Covid-19 pandemic. Learning tools developed include 1) lesson plans used for, 2) Student Books, and 3) Worksheets. The research was conducted at SMP Muhammadiyah Enrekang with the research subjects being Class VII students in the 2019/2020 Academic Year. The development of the learning tool refers to four D Models (4-D models) consisting of four stages, namely defining, designing, developing, and disseminating. The process of research and dissemination of instruments is done online by using the Zoom, Whatsapp, and Google Form. At the design stage, the draft RPP produced 4 meetings, Student Books, and Student Workbooks. The development stage through the expert validation stage and field trials is obtained: 1) The results of the expert validation showed that the lesson plan, Student Book, and Worksheet are good and can be used with minor revisions; 2) The results of the field trials showed that lesson plans, student books, and worksheets did not need to be revised. Whereas for positive student responses and learning outcomes tests seen from classical completeness obtained was quite feasible to use. The products from this research are valid, practical, and effective learning tools for set material.